Pro-Environmental Behavior of Consumers - PODVORICA, Ganimete; UKAJ, Fatos (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019DO - 10.14505//jemt.v10.1(33).01, 2019)
This paper reports the results of a survey on pro-environmental behaviour of consumers within the urban zones of Kosovo. The objective of the study is to explore consumers’ affordability to purchase environmentally friendly products based on the gender roles and investigates the correlation of the consumers who consider that such purchases contribute to the environmental protection including local participation at environmental movements regarding efficient energy use and water efficiency. Findings reveal that despite low-involvement of consumers to environmental movements on efficient energy use and water efficiency initiated by environmental non-governmental organizations, there remains a lack of empirical research on national institutional environmental initiatives to promote and motivate pro-environmental behavior of consumers and create informed citizenry. This research presents the opportunity for further exploration of dimensions regarding product related pro-environmental consumers’ behavior and motivation factors.